Wide bandwidth and flat multiwavelength Brillouin-erbium fiber laser - Al-Alimi, A. W.; Cholan, N. A.; Yaacob, M. H.; Abas, A. F.; Alresheedi, M. T.; Mahdi, M. A. (Optical Society of America, 2017)
A wide bandwidth and flat multiwavelength Brillouin-erbium fiber laser is demonstrated experimentally. In the proposed laser setup, the combination of a Brillouin mirror with feedback and a ring cavity with four-wave mixing assistance is realized. The efficiency of Brillouin Stokes lines generation is enhanced by the feedback-based Brillouin mirror structure. The effect of four-wave mixing in highly nonlinear fiber increases the generation of Brillouin Stokes lines in a wider bandwidth. The laser lines over 16 nm bandwidth (i.e 200 channels) within 4.65 dB power difference are obtained. The generated laser lines span from 1534 to 1550 nm with wavelength spacing of 0.08 nm and optical signal-to-noise ratio of at least 15 dB. The laser can also be freely tuned over 32 nm and is stable with power fluctuations of 0.7 dB over 1 hour duration.